Polemik Usia Baligh Sebagai Kriteria Pemimpin Dalam Fikih Islam - Ahmad, Ahmad; Agus Muchsin; Muh Nur Hidayat; Usman; Haidir Hasba (Maqasid: Jurnal Studi Hukum Islam, 2025)
This study examines the polemic surrounding the concept of puberty (baligh) as a criterion for leadership in Islamic jurisprudence (fiqh). In classical Islamic fiqh, baligh marks the onset of religious and legal accountability (mukallaf), typically indicated by biological signs or an age threshold of 15-18 years, as outlined in texts like Safinatun Najah and Al-Fiqh ‘Alā Al-Mażāhib Al-Arba’ah. However, its application as a leadership criterion sparks debate due to varying interpretations across the Syafi’i, Hanafi, Maliki, and Hambali schools, particularly regarding whether puberty alone suffices or requires additional qualifications like intellectual maturity, justice, and managerial competence. Using a qualitative library research approach, this study analyzes classical fiqh texts, Qur’anic verses (e.g., Surah An-Nur: 59), hadiths, and modern academic literature. Findings reveal that while baligh is a fundamental requirement, leadership in modern political contexts, such as Indonesia’s electoral laws (e.g., UU No. 7/2023), demands a holistic maturity encompassing intellectual, emotional, and spiritual dimensions. The study contributes to bridging classical fiqh with contemporary leadership needs, highlighting the necessity of reinterpreting baligh within a maqashid syariah framework to address modern governance complexities. Recommendations include integrating pre-baligh education to foster moral and intellectual readiness and further research into harmonizing fiqh-based criteria with democratic systems.   Keywords: Jurisprudence, Puberty (Baligh), Leadership Criteria, Age Maturity, Politics.